2014
DOI: 10.1590/01047760.201420021524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of particleboard panels manufactured with wood from Sequoia sempervirens and Pinus taeda

Abstract: AVALIAÇÃO DA QUALIDADE DE PAINÉIS AGLOMERADOS PRODUZIDOS COM MADEIRA DESequoia sempervirens E Pinus taeda RESUMO: O objetivo do presente trabalho foi avaliar as propriedades físicas e mecânicas de painéis aglomerados produzidos a partir de partículas de madeira de Sequoia sempervirens e Pinus taeda com resina uréia-formaldeido (UF) em diferentes proporções de mistura das duas espécies, sendo 100%, 0%, 75%, 50% e 25% de partículas de sequoia, respectivamente. Foram avaliadas as propriedades de massa específica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 2 publications
1
9
1
4
Order By: Relevance
“…There are no comparative values available in the literature for water absorption and thickness swelling for structural particleboards produced with resin moisture resistant. However, the mean values of TS 24 h obtained in this study were lower than the results reported by some researchers to pine boards produced with urea-formaldehyde resin: 18.61% (Trianoski et al, 2013); 24.22% (Iwakiri et al, 2014); 31.41% (Trianoski et al, 2016); 18.56% (Trianoski et al, 2011).…”
Section: /8contrasting
confidence: 74%
See 1 more Smart Citation
“…There are no comparative values available in the literature for water absorption and thickness swelling for structural particleboards produced with resin moisture resistant. However, the mean values of TS 24 h obtained in this study were lower than the results reported by some researchers to pine boards produced with urea-formaldehyde resin: 18.61% (Trianoski et al, 2013); 24.22% (Iwakiri et al, 2014); 31.41% (Trianoski et al, 2016); 18.56% (Trianoski et al, 2011).…”
Section: /8contrasting
confidence: 74%
“…All treatments met the minimum values of 800 N and 1,020 N, respectively for the RAP-T and RAP-S, as established by the ABNT-NBR 14810-2:2006. Although the comparative figures are not available in the literature for mechanical properties of structural particleboards produced with moisture resistant resin, the results obtained in this study were satisfactory in comparison to those presented by some researchers to pine boards produced with urea-formaldehyde resin. For the MOE, the values referenced were 1,581 MPa (Trianoski et al, 2011), 1,751 MPa (Trianoski et al, 2011) and 1,847 MPa (Iwakiri et al, 2014). For MOR the values were 11.17 MPa (Trianoski et al, 2011), 13.94 MPa (Trianoski et al, 2016) and 12.78 MPa (Iwakiri et al, 2014).…”
Section: /8mentioning
confidence: 99%
“…Iwakiri et al 21 have evaluated the physical and mechanical properties of particleboard panels manufactured with wood particles from Sequoia sempervirens and Pinus taeda combined with urea-formaldehyde resin (UF), using different mixing ratios. The findings achieved for internal bond, modulus of elasticity (MOE) and modulus of rupture (MOR) under static bending have met the minimum requirements of British Standard BS312:2003 in all treatments, revealing that Sequoia sempervirens has great potential for particleboard production 21 . In order to combine the mechanical performance of Pinus taeda and Sugarcane bagasse, hot-pressed hybrid sandwich particleboard panels were investigated in this work.…”
Section: Introductionmentioning
confidence: 99%
“…This seemed to happen because of the spread over of resin to a greater particle surface area instead of filling the voids existence inbetween the particles. According to [25], board with higher compaction ratio tends to have a more closed structure. As shown in Figure 4, TS of particleboards increased significantly with increasing board density.…”
Section: Resultsmentioning
confidence: 99%